The level of nurses’ knowledge regarding peripheral vascular access – is there a needfor further education in this area? - Grabowska, Hanna; Sójkowska, Paulina (Nursing in the 21st Century, 2025)
Aim. The aim of the study was to assess nurses’ knowledge regarding peripheral vascular access.Material and methods. The study was conducted among 153 individuals, predominantly women and urban residents. The average age of respondents was 30.6 years, and their average work experience in the profession was 7.9 years. More than half of the respondents held a bachelor’s degree in nursing. The study utilised a diagnostic survey method and a questionnaire technique. The analysis included the Shapiro-Wilk test, the Mann-Whitney U test, the Kruskal-Wallis H test, and the chi-square test.Results. A high and very high level of knowledge was demonstrated by 35 (22.9%) and 43 (28.1%) respondents, respectively. The average number of correct answers was 19.4 points. The highest number of correct responses was given to questions concerning the essence, purpose, legal foundations, and principles of caring for a patient with a short peripheral intravenous catheter, while fewer correct answers were given regarding the use of midline catheters.Conclusions. The respondents demonstrated a relatively high overall level of knowledge regarding peripheral vascular access. A significant impact of age, place of residence, work experience in the nursing profession, and the type of pre- and postgraduate education completed on the level of knowledge presented was observed.